2017
DOI: 10.1016/j.bjhh.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, cost per donation and reduction in blood supply due to positive and indeterminate results for infectious markers in a blood bank in Lima, Peru

Abstract: IntroductionSafety in Transfusion Medicine is subject to regulations and government legislation within a total quality framework. The aim of this study was to evaluate the impact of seroprevalence and indeterminate results on lost units and cost per donation.MethodsA prospective cross-sectional study was performed in the Blood Bank and Transfusion Therapy Department of the Hospital Central de la Policia Nacional del Perú in Lima, Peru. All completed donations (replacement/voluntary) without complications were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the case of Chagas disease, the set of evidence consolidated by several studies advocates in favor of serological testing of donors in blood bank as well as in antenatal screening [20][21][22][23][24][25][26][27][28] as cost-effective public health strategies. These results corroborate the resolution of the World Health Assembly, which recommends Chagas disease screening for pregnant women in non-endemic areas if they were born in disease-endemic areas, if they have lived for a long time in disease-endemic areas, or if they were born to mothers who lived in disease-endemic areas 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Chagas disease, the set of evidence consolidated by several studies advocates in favor of serological testing of donors in blood bank as well as in antenatal screening [20][21][22][23][24][25][26][27][28] as cost-effective public health strategies. These results corroborate the resolution of the World Health Assembly, which recommends Chagas disease screening for pregnant women in non-endemic areas if they were born in disease-endemic areas, if they have lived for a long time in disease-endemic areas, or if they were born to mothers who lived in disease-endemic areas 57 .…”
Section: Discussionmentioning
confidence: 99%
“…In Peru, Moya-Salazar et al 25 evaluated the impact of seroprevalence and indeterminate results on lost units and cost per donation. A total of 7,723 donations were evaluated and the total loss was of 49,750 US dollars.…”
Section: Economic Analysis On Diagnosis Diagnosis and Treatment Or Treatmentmentioning
confidence: 99%
“…In France, a non-endemic area, a study in 2011 by the French Blood bank [13] showed that, among the 163,740 donations that had been tested for Chagas disease (3.5% of the total donations), five were positive and close to 1400 indeterminate (0.85%). In Peru, a recent study [14] showed that, of 7723 donations evaluated for Chagas disease in 2014 to 2015, ten were positive (overall prevalence 0.14%) and 98 indeterminate (overall prevalence 1.27%). In both of these examples, the number of indeterminate results was superior to that of the positive results.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the quality requirements of public and private Hemotherapy and Blood Bank centres, there is the imperative to know the needs and health realities of its users and to effectively meet all the requirements of cancer patients. Therefore, the Blood Banks must possess stocks of the most demanded blood products and a constant flow of high-quality pathogen-free donations [ 27 ].…”
Section: Discussionmentioning
confidence: 99%